Bicara Cendekiawan Mulia UMP discusses current issues - UMP, PNC (2020)
Universiti Malaysia Pahang (UMP) organised the Bicara Cendekiawan Mulia UMP programme discussing the topic of “Terrorism: Influences and Threats in the Country”, presented by the Bukit Aman Special Branch Counter-Terrorism Division (E8) chief, Datuk Ayob Khan Mydin Pitchay.